A metastatic G2 neuroendocrine tumor smaller than 5 mm: A case report. (May 2022) - Inoue, Manabu; Tsukamoto, Shunsuke; Moritani, Konosuke; Sekine, Hideki; Saito, Yutaka; Kanemitsu, Yukihide
Abstract: Background: Neuroendocrine tumors (NETs) measuring <10 mm are widely thought to be at low risk of lymph node metastasis. Here we report a case of lymph node metastasis in a patient with a 4-mm NET that was classified as grade 2. Presentation of case: A 32-year-old woman was referred to our hospital after a positive fecal occult blood test. Colonoscopy revealed a 4-mm yellowish submucosal tumor, which was diagnosed as NET of the upper rectum and removed by endoscopic submucosal resection with ligation. Pathological examination of the specimen showed a 4-mm grade 2 NET with a Ki-67 labeling index of 4.4% without lymphatic or venous invasion. In accordance with the European Neuroendocrine Tumor Society guidelines, we performed robotic-assisted laparoscopic low anterior resection with lymph node dissection. Final pathological examination revealed invasion confined to the submucosal layer and metastasis to one lymph node (pT1aN1M0, Stage IIIB). There were no residual tumor cells in the scar after endoscopic submucosal resection with ligation. Discussion: Should G2 neuroendocrine tumors smaller than 5 mm be surgically resected? Conclusions: We encountered a rare case of a small NET with lymph node metastasis that was treated by robotic-assisted laparoscopic low anterior resection with lymph node dissection. Additional surgery is an option to be considered for grade 2 NET even if it is small because of the possibility of lymph node metastasis. Highlights: The treatment strategy for very small NET G2 (less than 5 mm) is still controversial. Rectal NET G2 can spread to lymph nodes even if it is small. NETG2, even if small, may be an indication for additional surgery. Minimally invasive surgery is a good indication for additional resection.